To solve this system of equations, we can use the method of substitution or elimination. Let's use the substitution method in this case.
1. Solve the first equation for y:
-6x + 2y = -32
2y = 6x - 32
y = 3x - 16
2. Substitute this expression for y into the second equation:
4x + 3(3x - 16) = -9
4x + 9x - 48 = -9
13x - 48 = -9
13x = 39
x = 3
3. Substitute the value of x back into the first equation to solve for y:
-6(3) + 2y = -32
-18 + 2y = -32
2y = -14
y = -7
Therefore, the solution to the system of equations is x = 3 and y = -7.
solve the system of equations -6x + 2y=-32 4x+3y=-9
1 answer